The Photovoltaic Properties Of A Good Rectifying Al/n-zno/p-si/al Schottky Diode Used In Solar Cell - Benhaliliba, M. (University of Eloued جامعة الوادي, 2017)
The photovoltaic properties of a good rectifying Al/ZnO/pSi/Al Schottky diode are studied. The diode was fabricated from two processes like ultrasonic spray pyrolysis @ 350°C for the ZnO layer on p-type Si substrate and thermal evaporation in vacuum at 10-6Torr for the metallic contacts. The current-voltage (I-V) measurements show a good rectifying behavior. Therefore, the extracted parameters are calculated in dark and illumination in one hand and under heating conditions in other hand. Ideality factor is lower around 1.5. Barrier height and series resistance, determined by Cheung-Cheung and Norde methods, are found to be 0.6-0.9 V and 1.4-5.4 kΩ. The parameters are influenced by increasing temperature; barrier height goes from 0.7 to 0.9 V and series resistance range within the range 1.2 -2.5 kΩ. Under light (150 W), the open circuit voltage and short circuit are found to be 0.09 V and 0.3 µA, the fill factor is of 0.44.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Schottky barrier diode; the sprayed ZnO film; Current-voltage characteristics; Good rectifying behavior; Open circuit voltage; Barrier height; Series resistance.